Nurses’ workarounds in acute healthcare settings: a scoping review - Debono, Deborah S (BioMed Central, 2013)
BACKGROUND: Workarounds circumvent or temporarily ‘fix’ perceived workflow hindrances to meet a goal or to achieve it more readily. Behaviours fitting the definition of workarounds often include violations, deviations, problem solving, improvisations, procedural failures and shortcuts. Clinicians implement workarounds in response to the complexity of delivering patient care. One imperative to understand workarounds lies in their influence on patient safety. This paper assesses the peer reviewed empirical evidence available on the use, proliferation, conceptualisation, rationalisation and perceived impact of nurses’ use of workarounds in acute care settings. METHODS: A literature assessment was undertaken in 2011–2012. Snowballing technique, reference tracking, and a systematic search of twelve academic databases were conducted to identify peer reviewed published studies in acute care settings examining nurses’ workarounds. Selection criteria were applied across three phases. 58 studies were included in the final analysis and synthesis. Using an analytic frame, these studies were interrogated for: workarounds implemented in acute care settings by nurses; factors contributing to the development and proliferation of workarounds; the perceived impact of workarounds; and empirical evidence of nurses’ conceptualisation and rationalisation of workarounds. RESULTS: The majority of studies examining nurses’ workarounds have been published since 2008, predominantly in the United States. Studies conducted across a variety of acute care settings use diverse data collection methods. Nurses’ workarounds, primarily perceived negatively, are both individually and collectively enacted. Organisational, work process, patient-related, individual, social and professional factors contribute to the proliferation of workarounds. Group norms, local and organisational culture, ‘being competent’, and collegiality influence the implementation of workarounds. CONCLUSION: Workarounds enable, yet potentially compromise, the execution of patient care. In some contexts such improvisations may be deemed necessary to the successful implementation of quality care, in others they are counterproductive. Workarounds have individual and cooperative characteristics. Few studies examine nurses’ individual and collective conceptualisation and rationalisation of workarounds or measure their impact. The importance of displaying competency (image management), collegiality and organisational and cultural norms play a role in nurses’ use of workarounds.